Adaptation of Orcinus orca to underwater echolocation and vocalization - Mészáros Dorottya (2021)
The aim of my dissertation was to give an overview of the adaptation of Orcinus orca to the aquatic realm. Through the evolutionary changes that have taken place in the body structure, especially the transformation that are relevant in the appearance of echolocation and vocalization. Also, to describe the operation, function and variation of these two acoustic capabilities.